2021
DOI: 10.2147/ott.s282842
|View full text |Cite
|
Sign up to set email alerts
|

FLT3-ITD Mutation and FLT3 Ligand Plasma Level Were Not Associated with One-Year Survival of Indonesian Acute Myeloid Leukemia Patients

Abstract: Objective To analyze the association of FLT3-ITD mutation and FLT3 ligand plasma level with one-year survival of Indonesian acute myeloid leukemia (AML) patients. Methods A prospective cohort study was conducted to determine the association between FLT-3-ITD mutation and FLT3 ligand plasma level with one-year survival of Indonesian AML patients. In the study, a total of 51 AML patients were obtained from two tertiary hospitals in Indonesia from year 2018 to 2020. Inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The frequency of FLT3-ITD mutations in AML patients is known to be around 20-30% [ 6 ]. In a study conducted by Rinaldi et al, it was observed that the frequency of FLT3-ITD mutations in Indonesia is 21.5% in AML patients [ 24 ].…”
Section: Reviewmentioning
confidence: 99%
“…The frequency of FLT3-ITD mutations in AML patients is known to be around 20-30% [ 6 ]. In a study conducted by Rinaldi et al, it was observed that the frequency of FLT3-ITD mutations in Indonesia is 21.5% in AML patients [ 24 ].…”
Section: Reviewmentioning
confidence: 99%
“…Therefore, it is safe to conclude that the effect of chemotherapy drugs on DC proliferation depends on the degree of lymphocyte inhibition. The greater the drug dose, the stronger the inhibition of lymphocytes and more significant the effect on DC proliferation ( Rinaldi et al, 2021 ).…”
Section: Anticancer Gold Compounds and The Immune Systemmentioning
confidence: 99%
“…Nam et al developed novel polydopamine-coated AuNPs as photothermal reagents with high photothermal efficiency, which can induce cancer cells to produce ICD in situ . Combined with traditional chemotherapy drugs, PTT can further enhance the anti-tumor immune effect in the whole body and inhibit the development of primary tumors and metastasis ( Rinaldi et al, 2021 ). Zhang et al developed a nanoparticle platform for PTT-induced tumor immunotherapy.…”
Section: Anticancer Gold Compounds and The Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation